Pengaruh Penerapan E-Samsat dan Sanksi Perpajakan terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor (Studi Kasus pada Wajib Pajak di Samsat Makassar) - Nurchalifah S (Program Studi Pendidikan Akuntansi, Fakultas Ekonomi, Universitas Negeri Makassar, 2023)
The Effect of E-Samsat Implementation and Tax Sanctions on Motor Vehicle Taxpayer Compliance which variables have the dominant effect on motor vehicle tax compliance. The variables in this study are the implementation of E-Samsat as the first independent variable , tax sanctions as the second independent variable , and motor vehicle taxpayer compliance as the dependent variable . The population in this study are motor vehicle taxpayers registered in the Makassar Samsat in 2020 as many as 2236 people.